1998
DOI: 10.1515/cclm.1998.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Glucocard Memory 2 and Accutrend® Sensor Blood Glucose Meters

Abstract: The performance and practicability of 2 blood glucose meters (Glucocard Memory 2 and Accutrend sensor) were evaluated. Both glucose meters produced acceptably precise results in the hyper- and normoglycaemic concentration ranges. In the hypoglycaemic concentration range, the imprecision of Accutrend sensor was much higher than recommended by the American Diabetes Association. Within-run coefficients of variation for Glucocard Memory 2 were 6.3%, 3.9% and 2.4% at glucose concentrations of 1.7 mmol/l, 5.8 mmol/l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Of these, hematocrit has been shown to be one of the most important for neonatal samples having an inverse relation to blood glucose as measured by bedside tests. Because this effect has been analyzed in detail by other studies [2,8,18], for ethical reasons we did not obtain an additional blood sample to evaluate the hematocrit at the time the blood was taken for glucose measurement. But, a subgroup-analysis of small-for-gestational-age (SGA) infants prone to have high hematocrit values revealed a similar distribution of the differences between the two tests for SGA compared to non-SGA infants (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, hematocrit has been shown to be one of the most important for neonatal samples having an inverse relation to blood glucose as measured by bedside tests. Because this effect has been analyzed in detail by other studies [2,8,18], for ethical reasons we did not obtain an additional blood sample to evaluate the hematocrit at the time the blood was taken for glucose measurement. But, a subgroup-analysis of small-for-gestational-age (SGA) infants prone to have high hematocrit values revealed a similar distribution of the differences between the two tests for SGA compared to non-SGA infants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although, a study using venous adult samples adjusted to different hematocrit values between 0.20 and 0.80 demonstrated that the effect of hematocrit on glucose determination disappeared in the hypoglycemic range [2]. The hematocrit dependency originates from the fact that laboratory tests usually measure glucose concentration (in plasma) while bedside tests measure glucose molality (in whole blood).…”
Section: Discussionmentioning
confidence: 99%
“…For 90.4% of the patients with tuberculosis (525 of 581) recruited by the population-based tuberculosis study, for whom a serum sample obtained after the diagnosis of tuberculosis was available, serum glucose determination was performed using Synchron CX5 Delta equipment (Beckman Coulter, Fullerton, CA) (11). Both methods have been found to correlate closely: within-run coefficients of variation between both methods have been 15.2, 5, and 1.2% at concentrations of 0.9, 4.2, and 19.6 mmol/l, respectively; and 96% of the Accutrend Sensor results have been found within 15% of the comparison method results (12). The same cutoff level was used for both capillary and venous blood samples.…”
Section: Measurement Of Glucose Concentrationmentioning
confidence: 99%
“…The majority of blood glucose concentrations (74%) were measured with the Bayer 850 blood gas analyzer (Bayer AG, Leverkusen, Germany), with the remaining measurements taken using the bedside GluoCard (Arkray, Inc., Kyoto, Japan) and i-Stat (Abbott Laboratories, Illinois, USA) devices. The reported coefficients of variation for glucose measurements for the blood gas analyzer, GlucoCard and i-Stat devices were 4.9% [34], 2.4-6.3% [35,36], and 2.0-3.5% [37] respectively.…”
Section: Patient Cohortmentioning
confidence: 98%